2001
DOI: 10.1063/1.1381054
|View full text |Cite
|
Sign up to set email alerts
|

Nature and properties of the Johari–Goldstein β-relaxation in the equilibrium liquid state of a class of glass-formers

Abstract: Previous dielectric relaxation measurements of glycerol and propylene carbonate and new results on propylene glycol performed below the conventional glass transition temperatures T g after long periods of aging all show that the excess wing ͑a second power law at higher frequencies͒ in the isothermal dielectric loss spectrum, develops into a shoulder. These results suggest that the excess wing, a characteristic feature of a variety of glass-formers, is the high frequency flank of a JohariGoldstein ␤-relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
302
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(357 citation statements)
references
References 65 publications
(55 reference statements)
37
302
0
Order By: Relevance
“…We believe that the behavior of the excess wing seen in Figure 3 (decoupling from the R-process under pressure) is related to the effect of pressure on the shape of R-peak. As discussed in detail elsewhere, [14][15][16] pressure changes the strength of intermolecular interactions (as reflected in the peak breadth), whereby the separation of the primary R-peak and the secondary (excess wing) relaxation increases. Also seen in Figure 4 is a broadening of the spectra with increasing τ R , attained by either higher pressure or lower temperature; similar behavior is observed in other glass formers.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the behavior of the excess wing seen in Figure 3 (decoupling from the R-process under pressure) is related to the effect of pressure on the shape of R-peak. As discussed in detail elsewhere, [14][15][16] pressure changes the strength of intermolecular interactions (as reflected in the peak breadth), whereby the separation of the primary R-peak and the secondary (excess wing) relaxation increases. Also seen in Figure 4 is a broadening of the spectra with increasing τ R , attained by either higher pressure or lower temperature; similar behavior is observed in other glass formers.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the stress-induced instantaneous flow of yield, recent experiments and numerical simulations also demonstrated that a glass subject to stress, which is much smaller than its normal yield strength, can also undergo an extreme slow flowing, which is hard to be detected within a short period of time due to the slowness [4][5][6][7] . On the other hand, the universal nano-scaled localized b-relaxation in metallic glassy state has been observed before the large-scale a-relaxation, which has been demonstrated to be related to the nano-scaled microscopic hidden flowing phenomenon [8][9][10][11][12] . However, the structural origin of the flowing phenomena in metallic glasses (MGs) such as the slow flowing and instantaneous flow of yield, elastic and plastic deformations, the transition between the b-relaxation to the a-relaxation and glass to supercooled liquid transition are not clear yet due to the lack of clear structural information.…”
mentioning
confidence: 99%
“…Recent studies on the atomic-scale glassy structure have revealed the existence of liquid-like sites in glassy state 4,18,19 , which are presumed to be responsible for the viscoelastic flow behaviour in glasses [20][21][22] . Meanwhile, the studies on glasses have demonstrated that the b-relaxation is identified to play an essential role in the GLT process 2,8,9,11,23 , and the b-relaxation has comparable activation energy with that of the deformation unit and strongly correlated with mechanical brittle-to-ductile transition in MGs 20,21,[24][25][26] , indicating that the b-relaxation is closely related to the initiation and evolution of the localized liquid-like deformation units or flow units in MGs [27][28][29][30] . Yet, the fraction and evolution of these liquid-like zones, leading to the flow phenomena such as elastic and plastic deformations and GLT, are still speculative due to the lack of abundant experimental evidence, and the intrinsic correlations between such deformation transition, relaxation mode and structural characteristics changes during GLT are still poorly understood.…”
mentioning
confidence: 99%
“…In fact, a correlation between the α-and β JG -relaxation times has been experimentally proven, based on empirical findings on a large number of glass formers. 27 According to these studies, the primitive JG relaxation time (τ JG ) is related to the α-relaxation time (τ α ) as:…”
Section: Resultsmentioning
confidence: 99%
“…Secondary relaxations in OD phases may have different origins; for example, the constituent molecules generally exhibit intramolecular dynamics, such as conformational motions or vibrations of inter-atomic bonds; in other cases a single-molecule precursor of the α process is observed, which is called Johari-Goldstein relaxation and is usually interpreted in the framework of the coupling model. [25][26][27] The spectral landscape of secondary relaxations of structural glass formers is further enriched by the existence of the so-called excess wing (EW), that is, of an excess dielectric loss on the highfrequency side of the α-relaxation process. 17,18,28,29 Based on comparative studies of several structural glass formers, some authors 30 have proposed that the EW could actually be a nonresolved secondary relaxation process hidden below the high-frequency wing of the primary α-relaxation.…”
Section: Introductionmentioning
confidence: 99%